Institusionalisasi Sovereign Social Endowment Fund: Model Integrasi Wakaf Produktif dan Reindeksasi Komoditas untuk Ketahanan Fiskal Hari Tua - Yepri Endika; Asih Endah Subandiyah (Scimadly Publishing, 2025)
This study aims to design a macro-structural framework for social security of institutionalizing the Sovereign Social Endowment Fund (SSEF) as a solution to deficit-ridden conventional pension systems. Employing a qualitative-conceptual method under the Maqasid Shariah framework, this paper evaluates institutional policy structures to protect public wealth and dignity. The main findings indicate that integrating Wakalah bil Ujrah and Mudharabah Musytarakah contracts successfully operationalizes the pillar of hifzh al-mal (protection of wealth) by constructing a bankruptcy-remote asset management system that legally isolates participants' funds from sovereign default risks. Furthermore, utilizing macro productive waqf as a permanent social endowment serves as an automatic fiscal stabilizer, effectively achieving hifzh al-nafs (protection of life and dignity) by safeguarding vulnerable elderly generations without expanding state debt or relying on fiscal budgets. The study also models a gold-based reindexation framework that shields long-term benefits from fiat currency inflation. As a substantive conceptual contribution to Islamic public finance, this paper bridges theoretical Maqasid Shariah with applied fiscal policy, proving that integrated Islamic social finance can create a self-sustaining national social protection ecosystem. This framework offers a practical policy roadmap for central banks and ministries of finance to build cross-generational distributive justice.